Digital Exclusion and the Structural Barriers to Safety Strategies among Men and Non-Binary Sex Workers Who Solicit Clients Online - Brett Koenig; Alka Murphy; Spencer Johnston; Jennie Pearson; Rod Knight; Mark Gilbert; Kate Shannon; Andrea Krüsi (Social Sciences, 2022)
Background: Evidence shows that online solicitation facilitates sex workers’ ability to mitigate the risk of workplace violence. However, little is known about how end-demand sex work criminalization and the regulation of online sex work sites shape men and non-binary sex workers’ ability to maintain their own safety while soliciting services online. Methods: We conducted 21 semi-structured interviews with men and non-binary sex workers in British Columbia between 2020–2021 and examined their ability to enact safety strategies online in the context of end-demand criminalization. Analysis drew on a structural determinants of health framework. Results: Most participants emphasized that sex work is not inherently dangerous and described how soliciting services online facilitated their ability to enact personal safety strategies and remain in control of client interactions. However, participants also described how end-demand criminalization, sex work stigma, and restrictive website policies compromise their ability to solicit services online and to enact safety strategies. Conclusions: Alongside calls to decriminalize sex work, these findings emphasize the need to normalize sex work as a form of labour, promote access to online solicitation among men and non-binary sex workers, and develop standards for online sex work platforms in partnership with sex workers that prioritize sex worker safety.